Dynamical Analysis of New Fractional Order ZIKV Model with Nonlinear Incidence Rate - Nurul Anggraeni Hidayati (Jurnal Riset Mahasiswa Matematika, 2025)
The ZIKV model provided is derived by adapting the model proposed by \cite{Hidayati2021}. This study enhances the existing model by transforming it into a fractional-order ZIKV model with a nonlinear incidence rate. The model's equilibrium points are identified, and the stability conditions for each point are evaluated using the Routh-Hurwitz criterion. A numerical simulation is performed to validate the stability study results. Numerical simulations further demonstrate the impact of the order $α$ on the stability of the equilibrium point inside the model.